2008
DOI: 10.1088/0264-9381/25/6/065001
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the volume operator in loop quantum gravity: I. Results

Abstract: We analyze the spectral properties of the volume operator of Ashtekar and Lewandowski in Loop Quantum Gravity, which is the quantum analogue of the classical volume expression for regions in three dimensional Riemannian space. Our analysis considers for the first time generic graph vertices of valence greater than four. Here we find that the geometry of the underlying vertex characterizes the spectral properties of the volume operator, in particular the presence of a 'volume gap' (a smallest non-zero eigenvalu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(111 citation statements)
references
References 62 publications
3
108
0
Order By: Relevance
“…The construction of the operator L I for finite ∆s and given cylindrical function is discussed in section 3.3.5. It requires two ingredients: the two-hand operatorŶ i Iαβ corresponding to the quantization of the quantity introduced in (30), and the inverse of the local volume operatorV I . These two ingredients enter in the definition of L I in the way specified by equations (29) and (31).…”
Section: Quantization Of the Regularized Expressionmentioning
confidence: 99%
“…The construction of the operator L I for finite ∆s and given cylindrical function is discussed in section 3.3.5. It requires two ingredients: the two-hand operatorŶ i Iαβ corresponding to the quantization of the quantity introduced in (30), and the inverse of the local volume operatorV I . These two ingredients enter in the definition of L I in the way specified by equations (29) and (31).…”
Section: Quantization Of the Regularized Expressionmentioning
confidence: 99%
“…The area operator and the volume operator in the context of loop quantum gravity have been considered in [44] for the first time. Further studies concerning the area operator can be found in [45], [46], [47] and concerning the volume operator in [48], [49], [50], [51], [52]. In this paper the considerations will remain restricted to the area operator.…”
Section: Holonomy Representation and Area Operatormentioning
confidence: 99%
“…The action of the remaining holonomies in (34) can be simplified by Theorem (loop trick) (36) where ði; j; kÞ ¼ 1 if the edges e i , e j , e k are ordered anticlockwise, otherwise it equals À1.…”
Section: A Action On Gauge-invariant Trivalent Verticesmentioning
confidence: 99%
“…Inserting this in the first equality proves the theorem. As in the example on page 11, adding h s k to (35) transforms the solid line c 1 into a dashed line so that with (36) and…”
Section: A Action On Gauge-invariant Trivalent Verticesmentioning
confidence: 99%
See 1 more Smart Citation